Zespoły bólowe kręgosłupa w grupie fizjoterapeutów = Spine pain syndromes in a group of physiotherapists - Radzimińska, Agnieszka; Weber-Rajek, Magdalena; Jaworska, Urszula; Goch, Aleksander; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Radzimińska Agnieszka, Weber-Rajek Magdalena, Jaworska Urszula, Goch Aleksander, Zukow Walery. Zespoły bólowe kręgosłupa w grupie fizjoterapeutów = Spine pain syndromes in a group of physiotherapists. Journal of Education, Health and Sport. 2016;6(6):553-564. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56691 http://ojs.ukw.edu.pl/index.php/johs/article/view/3643 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. Zespoły bólowe kręgosłupa w grupie fizjoterapeutów Spine pain syndromes in a group of physiotherapists Agnieszka Radzimińska1, Magdalena Weber-Rajek1, Urszula Jaworska1, Aleksander Goch2, Walery Zukow3 Katedra Fizjoterapii, Zakład Podstaw Fizjoterapii, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Katedra Fizjoterapii, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: zespół bólowy kręgosłupa, fizjoterapeuta. Keywords: spinal pain syndrome, physical therapist. Streszczenie Zgodnie z wynikami badań z 2005 roku przeprowadzonymi przez European Fundation for the Improvement of Living and Working Conditions (Europejską Fundację na Rzecz Poprawy Warunków Życia i Pracy) w krajach Unii Europejskiej najbardziej powszechnym problemem zdrowotnym związanym z pracą są dolegliwości mięśniowo-szkieletowe. Celem pracy była ocena stopnia niepełnosprawności będącej wynikiem bólu kręgosłupa w grupie zawodowej fizjoterapeutów. Narzędziem badawczym były: NDI (NECK DISABILITY INDEX) oraz ODI (OSWESTRY DISABILITY INDEX). Ocena stopnia niepełnosprawności mierzonej za pomocą kwestionariuszy ODI i NDI pozwoliła zakwalifikować fizjoterapeutów do przedziału wskazującego na łagodną niepełnosprawność. W badanej grupie dolegliwości bólowe kręgosłupa w odcinku szyjnym i lędźwiowym zwiększają się wraz z wiekiem oraz stażem pracy. Summary According to research conducted in 2005 by the European Foundation for the Improvement of Living and Working Conditions in the European Union the most common health problem is work-related musculoskeletal disorders. The aim of the study is to assess the degree of disability in the occupational group of physiotherapists, measured by questionnaires NDI (NECK DISABILITY INDEX) and ODI (OSWESTRY DISABILITY INDEX). Assessment of the degree of disability as measured by questionnaires ODI and NDI helped qualify physiotherapists compartment indicating a mild disability. Back pain in the cervical and lumbar increases with age and seniority.